On the influence of electrode erosion on properties of nonideal plasma of underwater discharges - Starchyk, P.D.; Porytskyy, P.V. (Вопросы атомной науки и техники, 2012)
It is considered the influence of electrode erosion vapors on the transport properties of a nonideal plasma of underwater discharges at high pressure. The experimental investigation is presented on erosion evaporation and penetration into plasma. The transport coefficient set based on the Grad’s method is compared with the data obtained by using of the Lorentzian plasma theory at the same plasma composition. Also, the calculation data are considered to be in reference with transport coefficients obtained by using the Chapman-Enskog’ method. It is pointed that the nonideality effects are needed to take into consideration under calculation of properties of underwater discharge.